2016
DOI: 10.1057/s41287-016-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of the Rich? The Social Patterning of Hypertension in Six Low- and Middle-Income Countries

Abstract: Introduction.Hypertension and non-communicable diseases (NCDs) are not as yet priority issues for international development. This is surprising, since NCDs already account for a higher share of mortality and illness in low and middle income countries (LMICs) than infectious diseases do, and are set to rapidly increase (WHO, 2010). Referring to the broader policy literature, the papers identifies reasons for this general neglect. These include a general perception that, in contrast to high income countries, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Consistent with our findings, other regional meta-analyses in Africa did not find significant sex differences [6, 10] while others reported higher male prevalence [5, 7]. In individual studies in older persons in Africa in which multivariable analyses were performed, female sex predicted a higher prevalence of hypertension [41, 43, 76, 77, 87] while in others sex was not independently associated with hypertension [49, 57, 67].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with our findings, other regional meta-analyses in Africa did not find significant sex differences [6, 10] while others reported higher male prevalence [5, 7]. In individual studies in older persons in Africa in which multivariable analyses were performed, female sex predicted a higher prevalence of hypertension [41, 43, 76, 77, 87] while in others sex was not independently associated with hypertension [49, 57, 67].…”
Section: Discussionsupporting
confidence: 90%
“…The increase in the prevalence of hypertension with age was rarely monotonic [65] and tended to peak in the middle or penultimate age group [49, 68, 72, 75]. In all the studies in which the relationship between age and hypertension was investigated through multivariate analysis, older age group was independently associated with hypertension [43, 57, 68, 76, 77].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were conducted between 2007 and 2016 and published between 2010 and 2017. The number of covariates evaluated for their association with the binomial outcome of hypertension in the models ranged from five [19, 30] to thirteen [20]. One study provided separate estimates for the prevalence of hypertension in two countries, Central African Republic (CAR) and the Congo [36].…”
Section: Resultsmentioning
confidence: 99%
“…In high income countries, evidence shows that NCDs are prevalent among those with low SES. Such vulnerabilities may be associated to poor access to healthcare, psychosocial stress, lack of awareness and control of NCDs (Lloyd-Sherlock et al 2017). However, despite these concurrent findings, a cross country study in six countries found that hypertension was more prevalent among rich elderly Ghanaians (Stringhini et al 2016).…”
Section: Discussionmentioning
confidence: 99%